Pengaruh Promosi Penjualan Terhadap Keputusan Pembelian Pada CV. Pelangi Media Pustaka - Hermanto, Gabriel Frengki; Rahmat, Yogie (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This study aims to determine the effect of sales promotion on purchasing decisions at CV. Pelangi Media Pustaka Pekanbaru. Using a total sample of 100 people. In this study, the author uses a quantitative descriptive research method using the SPSS method. From the results obtained t count of the sales promotion variable is 7.261 and the t table value is 1.66055. So t count > t table (7.261 > 1.66055) and a significant value of 0.00 < 0.05, so it can be concluded that the sales promotion variable can influence consumer purchasing decisions. In testing the coefficient of determination (R) obtained a value of R = 0.591 means the relationship between the independent variable (sales promotion) to the dependent variable (consumer purchasing decisions) is 35% and while the remaining 65% is influenced by other variables that are not careful. Finally, from this study it can be concluded that sales promotion has a significant influence on purchasing decisions in consumers, so it is recommended to CV. Pelangi Media Pustaka Pekanbaru can improve sales promotions to improve consumer purchasing decisions and achieve company goals.